(3GdWhGFa aj eYQaI ePGgH GdWhGFas - (3GdMSjfj, GHf WGhhS, GHf WGhhS, Ydj Hf ehSi Hf LYaQ GdMSjfj, J (B664(3g` (B1266(3es
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg ceG jSJMb dPGJg hjSJhLHg HEMSGfg Edi eNdhbGJg (B... (3CJGfj QLd ef Cgd GdPeI (B... (3SeYJ GNJdGa Cgd Gdedc aj cd ReGfs
(3BNQgG (B:s
(3BNQgG(B: (3JfcQ GdCMGOjK GdcGPHI GdHGWdI hGdCbhGd (B... (3hJfaQ efgG hJfRg fHjge hGgd HjJg Ydjge GdSdGe hUMGHJg (B... (3ef gPg GdefGbVGJ hGdeYGQVGJ YfO ef jfXQ HYjf GdGfUGa Edi JMbjb CehQ Cgd GdOjGfGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 26s
(3GdPQjYI, L (B15: 112s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds